Metodología para determinar atributos y métricas de calidad en sistemas hipermedia adaptativos educativos basados en estilos de aprendizaje - Leighton Álvarez, Helmut (2011)
This study is a methodological proposal for determining the attributes and metrics of quality in adaptative educational hypermedia systems based on learning styles, specifically,concerning the active, reflexive, theoretical and pragmatic styles. These attributes and metrics refer only to the interaction of the user-student with the system, i.e., the study is done from a purely educational perspective, not from the perspective of the computer as a tool. Thus, the analysis takes as a starting point the characteristic o the learning style. Based on this, he attributes are established in accordance with the corresponding instructional strategies. Finally, the metrics needed for each of the attributes are defined, and the types of variables involved, their units of measurement and sales are established. In this way a cascade methodology is developed for determining attributes and metrics.